ANALISIS KINERJA KEUANGAN PADA BADAN LAYANAN UMUM DAERAH (BLUD) PUSAT KESEHATAN MASYARAKAT KEJAJAR 1 WONOSOBO (PERIODE 2016-2020) - Sulastiningsih Sulastiningsih; Agung Slamet Prasetyo; Ema Suprihatin (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The measurement of health service organization performance is important to discover because it can provide a good quality health services so that a good degree of health is achieved. This is a descriptive quantitative research that aims to measure and analyze the performance of the Kejajar 1 Public Health Center in 2016-2020 in terms of financial performance using 8 measurements which are cash ratio, current ratio, collection period, fixed asset turnover ratio, return on fixed asset ratio, return on equity, inventory turnover and PNBP ratio to operating expenses. The results of this study show that the average value of the ratio fluctuates from year to year, especially in 2020 due to the impact of the covid-19 pandemic. If viewed based on the categorization of scores, the performance of the Kejajar 1 Health Center from 2016 to 2020 is classified as a moderate category which tends to be good.